Management of coronary artery disease in Kyrgyzstan: a comparison with Turkey and europe according to European Action on Primary and Secondary Prevention by Intervention to Reduce Events III results - Rasim Kutlu; Tolkun Murataliev Muratalievic; Mehmet Erdem Memetoglu (KARE Publishing, 2014)
Objectives: The European Action on Primary and Secondary Prevention by Intervention to Reduce Events (EUROASPIRE III) Study in coronary artery disease had been undertaken between the years of 2006 and 2007, with the participation of 22 countries in Europe including Turkey (76 centers). In this study, the situation in the management of coronary artery disease in Kyrgyzstan was compared with EUROASPIRE III findings of Turkey and Europe. Study design: The results of 1067 patients with stable coronary artery disease admitted to 22 centers in Kyrgyzstan were studied retrospectively and compared with the European and Turkish findings in EUROASPIRE III. During the study, the patients were interviewed and examined in the first year after the initial coronary event and/or intervention. Results: The gender distribution of the 1067 patients in the study was 658 female (61.7%) and 409 male (38.3%), and the average age was 68+-14 years. The ratio of young patients (<50 years) in Kyrgyzstan and Turkey were higher compared with the other European countries (Kyrgyzstan 28.2%, Turkey 20% and Europe 12.7%). The number of patients followed after the coronary event in Kyrgyzstan was 524 (49.1%). Although there was not a big difference of the classical risk factors between Turkey and Europe, in Kyrgyzstan, smoking (75%), hypertension (84%), dyslipidemia (86.5%), and diabetes (74.4%) were much higher when compared to the other countries. The biggest difference between Kyrgyzstan and the other countries in EUROASPIRE III study including Turkey, was the infrequency of medical (78% vs. 95%) and interventional treatment (1.9% vs. 57%). Also, smoking cessation (27.4% vs.70.8% in Europe), physical activity (17.5% vs. 59.1% in Europe), and weight loss (37.2% vs. 58.2% in Europe) ratios after the coronary event were found to be much lower in Kyrgyzstan than in EUROASPIRE III study. Conclusion: When compared to the results of EUROASPIRE III study of Turkey and Europe; the Kyrgyzstan results were found to be behind for the prevention, follow-up and treatment goals set by the guidelines.